A room temperature stable non-crystallized liquid crystal tilted helical material and its application
By synthesizing a material system of liquid crystal dimer materials, nematic liquid crystal monomer materials and chiral molecules with specific ratios, the problem of crystallization instability of liquid crystal tilted helical structure at room temperature is solved, and the room temperature stability of the material and the long-term stability of physical parameters are achieved.
Patent Information
- Application Number
- CN202310908656.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-07-24
AI Technical Summary
The liquid crystal tilted helical structure material has crystallization instability at room temperature, which limits its application and promotion.
By synthesizing a material system consisting of liquid crystal dimer material, nematic liquid crystal monomer material and chiral molecules, the specific ratio is 35% to 55%, nematic liquid crystal monomer material, 40% to 60%, and chiral molecules 0.1% to 10%, to achieve a room temperature stable crystal tilted helical structure without crystallization.
It achieves extremely high stability of the material system at room temperature, maintains an ultra-low bending elastic constant, ensures that the material does not crystallize under storage conditions of more than one year, and maintains the stability of physical parameters.
Smart Images

Figure CN117070228B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and in particular relates to a room temperature stable non-crystallized liquid crystal tilted helical material and application thereof. Background Art
[0002] Liquid crystal tilted helical structure is a very promising photonic material. It has attracted great attention in recent years due to its low electric field driven wide dynamic range reflection band modulation performance. The tilted helical structure is a special chiral nematic phase liquid crystal state. When the material system meets the abnormally low bending elastic constant (K 33 <1pN), a tilted spiral structure can be constructed with the help of an external electric field. In the tilted spiral structure, the liquid crystal molecules spontaneously spirally arrange to form a one-dimensional spiral periodic structure along the direction of the electric field, and form a specific tilt angle θ with the direction of the spiral axis, where the pitch of the spiral is called the pitch P. This special molecular assembly behavior allows the tilt angle θ and pitch P in the tilted spiral structure to be reversibly modulated over a wide range according to changes in the electric field intensity, thereby manifesting as spectral modulation within a wide dynamic range controlled by a low electric field. This spectral modulation range can start from the near-ultraviolet band, cover the entire visible light band, and extend to the near-infrared band, with a total spectral modulation range of more than 600nm, and this electric field modulation behavior has almost no spectral distortion. The traditional electric field modulation behavior of the cholesteric phase spiral structure usually faces bottleneck problems such as a narrow spectral modulation range (<50nm), high driving voltage, and spectral distortion. Therefore, the unique electric field modulation property of the tilted spiral structure has also inspired a series of innovative photonic technologies based on the tilted spiral structure, including spectral filtering, tunable laser microcavity, information encryption, nonlinear optics and dynamically adjustable planar optics applications.
[0003] At present, the biggest challenge facing the industrial application of the tilted helix structure is the instability of the crystallization of its material system at room temperature. The tilted helix material system is usually composed of three parts: 1) the most necessary liquid crystal dimer material, which is used to provide the ultra-low bending elastic constant necessary for constructing the tilted helix; 2) conventional nematic liquid crystal materials, which are used to further modify the cholesteric phase temperature range, photoelectric anisotropy and other physical parameters of the material system; 3) chiral additives, which are used to provide an initial chiral environment and helical twisting force.
[0004] Liquid crystal dimer materials have ultra-low bending elastic constants due to their unique molecular configuration, which is a necessary condition for the formation of tilted helices. However, the nematic phase temperature range of liquid crystal dimer materials is usually extremely high and the temperature range is extremely narrow. For example, the most typical liquid crystal dimer material CB7CB has a nematic phase between 104-117°C, which greatly limits its application scenarios. Although the nematic phase temperature can be lowered and the phase range can be widened through molecular design, it is still a long way from room temperature, and molecular design usually has a long R&D cycle and high R&D risks, and faces difficulties such as new molecular design, synthesis, and purification. On the other hand, by mixing traditional nematic phase liquid crystal materials (for example, 5CB liquid crystal, E7 liquid crystal, etc.) with liquid crystal dimer materials, the nematic phase temperature of the material system can be effectively reduced and the phase range can be widened, so that it covers room temperature and maintains an ultra-low bending elastic constant. Although liquid crystal dimer materials have very good miscibility with traditional nematic phase liquid crystal materials, the material system is very unstable at room temperature, and usually crystallizes within a few hours, causing structural collapse. This is mainly due to the instability of liquid crystal dimer materials at low temperatures. Currently, there is still no substantial molecular design or process optimization to solve the above problem. Summary of the invention
[0005] The purpose of the present invention is to provide a room temperature stable non-crystallized liquid crystal tilted helical material, which solves the bottleneck problem that has long restricted the application of tilted helical structures and is a key technological breakthrough in pushing it towards engineering and even mass production.
[0006] Another object of the present invention is to provide an application of the room temperature stable and non-crystallized liquid crystal tilted helical material in the preparation of a display panel or a display device.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect of the present invention, a room temperature stable non-crystallized liquid crystal tilted helical material is provided, which is made of the following components in percentage by weight: 35% to 55% of liquid crystal dimer material, 40% to 60% of nematic phase liquid crystal monomer material, and 0.1% to 10% of chiral molecules;
[0009] The liquid crystal dimer material is CBnCB, where n is selected from a positive integer from 3 to 15 (such as 3, 4, 5, 6, 7, 8, 9, 10, 11, 12); the structure is as follows:
[0010]
[0011] The nematic liquid crystal monomer material is selected from 5CB, 8CB, 7OCB, E7, TEB300, SLC1717, SLC9023, HTD028200-200;
[0012] The structure of 5CB is as follows:
[0013]
[0014] The structure of 8CB is as follows:
[0015]
[0016] The structure of 7OCB is as follows:
[0017]
[0018] E7 was purchased from Jiangsu Hecheng, Shijiazhuang Chengzhi Yonghua, Yantai Xianhua, Merck, Germany, etc.; TEB300, SLC1717, SLC9023 were purchased from Shijiazhuang Chengzhi Yonghua Company; HTD028200-200 was purchased from Jiangsu Hecheng Company.
[0019] The chiral molecule is selected from CB15, R811, S811, R2011, S2011, R1011, S1011, R5011, and S5011.
[0020] The structure of CB15 is as follows:
[0021]
[0022] The structure of R811 is as follows:
[0023]
[0024] The structure of S811 is as follows:
[0025]
[0026] The structure of R1011 is as follows:
[0027]
[0028] The structure of S1011 is as follows:
[0029]
[0030] The structure of R2011 is as follows:
[0031]
[0032] The structure of S2011 is as follows:
[0033]
[0034] The structure of R5011 is as follows:
[0035]
[0036] The structure of S5011 is as follows:
[0037]
[0038] The chiral molecules are all purchased commercially, and the suppliers can be selected from Jiangsu Hecheng, Shijiazhuang Chengzhi Yonghua, Yantai Xianhua, Merck of Germany and other companies.
[0039] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 30% to 75%, CB9CB 15% to 45%, CB11CB 5% to 25%;
[0040] The structure of CB7CB is as follows:
[0041]
[0042] The structure of CB9CB is as follows:
[0043]
[0044] The structure of CB11CB is as follows:
[0045]
[0046] The room temperature stable non-crystallized liquid crystal tilted helical material is made of the following components in percentage by mass: 40-50% of liquid crystal dimer material, 45-55% of nematic phase liquid crystal monomer material, and 1-5% of chiral molecules.
[0047] The room temperature stable non-crystallized liquid crystal tilted helical material is made of the following components in percentage by weight: 45% of liquid crystal dimer material, 52% of nematic phase liquid crystal monomer material, and 3% of chiral molecules.
[0048] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 40% to 60%, CB9CB 20% to 40%, and CB11CB 10% to 20%.
[0049] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0050] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 40%, CB11CB 20%.
[0051] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 50%, CB9CB 35%, CB11CB 15%.
[0052] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 55%, CB9CB 30%, CB11CB 15%.
[0053] In the present invention, the liquid crystal dimer material can provide a desired ultra-low bending elastic constant and inhibit crystallization; the nematic phase liquid crystal monomer material can reduce the nematic phase temperature range and modify the physical parameters of the material system; the chiral molecules can construct an initial chiral environment to form a chiral nematic phase, and according to the difference in the helical twisting force of the chiral molecules and the left-right hand of the chirality, specific chiral molecules can be selected and the content of the chiral molecules can be adjusted.
[0054] The second aspect of the present invention provides an application of the room temperature stable and non-crystallized liquid crystal tilted helical material in the preparation of a display panel and a display device.
[0055] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:
[0056] The room temperature stable non-crystallized liquid crystal tilted helical material of the present invention has an overall chiral nematic phase temperature range covering room temperature 25°C. The material system is extremely stable and no crystallization occurs even if stored at room temperature for more than one year. The material system satisfies an extremely low bending elastic constant, and its K 33 <0.4pN; the physical parameters of the material system including dielectric constant and elastic constant remain stable and do not fluctuate with storage. Even after being stored for one year, the physical parameters of the material system of the present invention do not change significantly.
[0057] The room temperature stable non-crystallized liquid crystal tilted helical material of the present invention exhibits wide dynamic selective reflection modulation driven by low electric field (<2V / μm), and its reflection band modulation range is from 430nm to 1050nm, exceeding 600nm. The modulation of the wide spectrum under the action of the electric field still exhibits extremely strong stability. After the material system is stored for one year, the reflection spectrum band corresponding to the electric field intensity almost presents a one-to-one correspondence relationship, and there is no obvious difference.
[0058] The nematic phase temperature range of the existing material system is relatively high, usually existing above 100° C. The nematic phase of the room temperature stable non-crystalline liquid crystal tilted helical material of the present invention covers room temperature.
[0059] The existing material system is very unstable at room temperature, and usually crystallizes rapidly within a few hours, resulting in structural collapse and complete failure. The room temperature stable non-crystallized liquid crystal tilted helical material of the present invention is extremely stable, and no crystallization occurs even if stored at room temperature for more than one year;
[0060] The room temperature stable and non-crystallized liquid crystal tilted helical material of the present invention is prepared by mixing a plurality of relatively conventional liquid crystal dimers such as CB7CB, CB9CB, CB11CB and the like in a specific proportion, and by the synergistic effect between molecules and the complexity of the molecular conformation brought about by the molecular chain entanglement effect, the stability of the material system is effectively improved, thereby inhibiting crystallization. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a schematic diagram of the dielectric constant and elastic parameter results of the room temperature stable non-crystallized liquid crystal tilted helical material of the present invention tested at different time stages during storage for one year.
[0062] Figure 2 It is a schematic diagram of the reflection spectrum of the room temperature stable non-crystallized liquid crystal tilted helical material sample T-1 of the present invention during a storage period of one year as the reflection spectrum changes with electric field driving.
[0063] Figure 3 It is a schematic diagram of the electric field-driven reflection band of the tilted helical material system constructed by the room temperature stable non-crystallized liquid crystal tilted helical material sample T-1 of the present invention and the sample D-6 prepared in comparative example 9.
[0064] Figure 4 It is a schematic diagram of the polarizing microscope display results of the room temperature stable non-crystallized liquid crystal tilted helical material of the present invention.
[0065] Figure 5 It is a schematic diagram of the crystallization behavior of the conventional unstable inclined helical material comparative example 1 observed by naked eyes and verified by polarizing microscope. DETAILED DESCRIPTION
[0066] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0067] For the preparation of CBnCB in the examples of the present invention, see the literature: Liq. Cryst. 2017, 44, 127-146.
[0068] The synthetic route of CBnCB material is as follows:
[0069] Adipoyl chloride and 4-bromobiphenyl were added dropwise to a suspension of aluminum chloride / dichloromethane and stirred, the reaction mixture was added to water and shaken with dichloromethane. The remaining aqueous suspension was filtered, the solid was thoroughly washed with water and recrystallized from toluene. Triethylsilane was added dropwise to α,ω-bis(4'-bromobiphenyl-4-yl)butane and stirred in a trifluoroacetic acid and dichloromethane solution. The reaction mixture was allowed to reach room temperature and stirred for 48 hours, then the white solid was filtered off, washed with water and recrystallized from toluene. A mixture of α,ω-bis(4'-bromobiphenyl-4-yl)hexane, cuprous cyanide, and dry N-methylpyrrolidone was stirred at 200°C for 4 hours, then cooled to 80°C, and ferric chloride and hydrochloric acid were added. After stirring for another 30 minutes, the mixture was allowed to cool overnight, water was added, and it was shaken with dichloromethane. The organic layer was washed with water, dried over CaCl2 and the solvent was removed, and finally recrystallized from toluene.
[0070]
[0071] Example 1
[0072] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-1, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0073] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0074] The nematic liquid crystal monomer material is 5CB.
[0075] The chiral molecule is R811.
[0076] Example 2
[0077] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-4, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0078] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 40%, CB11CB 20%.
[0079] The nematic liquid crystal monomer material is 5CB.
[0080] The chiral molecule is R811.
[0081] Comparative Example 1
[0082] A material, named sample S-1, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0083] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 100%, CB9CB 0%, CB11CB 0%.
[0084] The nematic liquid crystal monomer material is 5CB.
[0085] The chiral molecule is R811.
[0086] Comparative Example 2
[0087] A material, named sample S-2, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0088] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 100%, CB11CB 0%.
[0089] The nematic liquid crystal monomer material is 5CB.
[0090] The chiral molecule is R811.
[0091] Comparative Example 3
[0092] A material, named sample S-2, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0093] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 0%, CB11CB 100%.
[0094] The nematic liquid crystal monomer material is 5CB.
[0095] The chiral molecule is R811.
[0096] Comparative Example 4
[0097] A material, named sample D-1, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0098] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 80%, CB9CB 20%, CB11CB 0%.
[0099] The nematic liquid crystal monomer material is 5CB.
[0100] The chiral molecule is R811.
[0101] Comparative Example 5
[0102] A material, named sample D-2, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0103] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 80%, CB9CB 0%, CB11CB 20%.
[0104] The nematic liquid crystal monomer material is 5CB.
[0105] The chiral molecule is R811.
[0106] Comparative Example 6
[0107] A material, named sample D-3, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0108] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 80%, CB11CB 20%.
[0109] The nematic liquid crystal monomer material is 5CB.
[0110] The chiral molecule is R811.
[0111] Comparative Example 7
[0112] A material, named sample D-4, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0113] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 20%, CB11CB 80%.
[0114] The nematic liquid crystal monomer material is 5CB.
[0115] The chiral molecule is R811.
[0116] Comparative Example 8
[0117] A material, named sample D-5, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0118] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 20%, CB9CB 0%, CB11CB 80%.
[0119] The nematic liquid crystal monomer material is 5CB.
[0120] The chiral molecule is R811.
[0121] Comparative Example 9
[0122] A material, named sample D-6, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0123] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 40%, CB11CB 0%.
[0124] The nematic liquid crystal monomer material is 5CB.
[0125] The chiral molecule is R811.
[0126] Comparative Example 10
[0127] A material, named sample D-7, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0128] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 0%, CB11CB 40%.
[0129] The nematic liquid crystal monomer material is 5CB.
[0130] The chiral molecule is R811.
[0131] Comparative Example 11
[0132] A material, named sample D-8, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0133] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 60%, CB11CB 40%.
[0134] The nematic liquid crystal monomer material is 5CB.
[0135] The chiral molecule is R811.
[0136] Comparative Example 12
[0137] A material, named sample D-9, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0138] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 0%, CB9CB 40%, CB11CB 60%.
[0139] The nematic liquid crystal monomer material is 5CB.
[0140] The chiral molecule is R811.
[0141] Comparative Example 13
[0142] A material, named sample D-10, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0143] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 60%, CB11CB 0%.
[0144] The nematic liquid crystal monomer material is 5CB.
[0145] The chiral molecule is R811.
[0146] Comparative Example 14
[0147] A material, named sample D-11, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0148] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 40%, CB9CB 0%, CB11CB 60%.
[0149] The nematic liquid crystal monomer material is 5CB.
[0150] The chiral molecule is R811.
[0151] Comparative Example 15
[0152] A material, named sample T-2, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0153] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 20%, CB9CB 60%, CB11CB 20%.
[0154] The nematic liquid crystal monomer material is 5CB.
[0155] The chiral molecule is R811.
[0156] Comparative Example 16
[0157] One material, named sample T-3, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0158] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 20%, CB9CB 20%, CB11CB 60%.
[0159] The nematic liquid crystal monomer material is 5CB.
[0160] The chiral molecule is R811.
[0161] Comparative Example 17
[0162] A material, named sample T-5, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0163] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 20%, CB11CB 40%.
[0164] The nematic liquid crystal monomer material is 5CB.
[0165] The chiral molecule is R811.
[0166] Comparative Example 18
[0167] One material, named sample T-6, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic liquid crystal monomer material, and 3% chiral molecule;
[0168] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 20%, CB9CB 40%, CB11CB 40%.
[0169] The nematic liquid crystal monomer material is 5CB.
[0170] The chiral molecule is R811.
[0171] Comparative Example 19
[0172] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-12, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0173] The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 80%, CB9CB 10%, CB11CB 10%.
[0174] The nematic liquid crystal monomer material is 5CB.
[0175] The chiral molecule is R811.
[0176] The results of the comparative experiments on the crystallization stability of the material systems prepared in the above examples and comparative examples are shown in Table 1:
[0177] The experimental steps for sample preparation and crystallization stability test are as follows:
[0178] First, all the samples were stirred at 130°C for 2 hours and poured into a commercial liquid crystal test box. The liquid crystal test box consists of two pieces of transparent glass coated with ITO electrodes and has a size of 18×15 mm. 2 , with an internal spacing of 12 μm. Subsequently, the sample was slowly cooled to room temperature of 25°C at a rate of 5°C / min. In order to eliminate the potential energy inside the material, a square wave electric field signal with a voltage of 10V and a frequency of 1kHz was applied to the sample for 10 minutes. The sample was then stored in a constant temperature and humidity chamber (25°C, 50%), and the crystallization of the sample was observed every day.
[0179] The crystallization time of a sample is defined as the time interval from the completion of sample preparation to the moment when the sample crystallization is first observed. The crystallization of the sample can be roughly measured by naked eye observation and verified by polarizing microscope. Figure 5 As shown, Figure 5 Schematic diagram of the crystallization behavior of conventional unstable inclined helical material comparative example 1 observed with naked eyes and verified by polarizing microscope. The figure shows a photo of the sample being crystallized and the morphology under a polarizing microscope. The uncrystallized area presents a relatively uniform texture. Once the sample begins to crystallize, a clear crystal structure is formed, such as the dendritic crystals shown in the figure.
[0180] Table 1
[0181]
[0182]
[0183] As can be seen from Table 1, when the mass percentage of the nematic phase liquid crystal monomer material reaches 52%, the material system exhibits a chiral nematic phase at room temperature 25°C. According to the composition and content of the liquid crystal dimer material CBnCB in the material system, the material system exhibits differentiated crystallization time. When the material ratio described in the present invention is met, it exhibits ultra-stable crystallization stability.
[0184] It can be proved from the data in Table 1 that when the material system contains only a single liquid crystal dimer material CBnCB, such as Comparative Examples 1 to 3, the material system is very unstable and crystallization will occur after only a few hours (samples S-1, S-2, S-3); when the material system contains two liquid crystal dimer materials CBnCB, the stability of the material system is improved, such as Comparative Examples 4 to 14. Among them, the sample prepared in Comparative Example 9 is the best, and can be maintained for 20 days without crystallization. However, the crystallization stability of the system is closely related to the content of CBnCB, and most of the material components still face the problem of poor stability. When the material system contains three liquid crystal dimer materials CBnCB, the stability of the material system is abnormally improved. Among them, sample T-1 prepared in Example 1 and sample T-4 prepared in Example 2 maintained 400 days without crystallization, and their stability was significantly enhanced. Comparative Examples 15, 16 and 19 crystallized on the 38th day, the 4th day and the 5th day, respectively, which is due to the high concentration of a single CBnCB in the system. This high concentration results in a material system (S-1, S-2, S-3) with stability close to that of a single dimer, which is extremely unstable and easily crystallized. Comparative Examples 17 and 18 crystallized on the 200th and 120th days, respectively, probably because the complex interactions between the molecules were not sufficient to establish an optimal balance to prevent crystallization. Therefore, the percentage and ratio between the three liquid crystal dimer materials in the present invention are crucial to the crystallization behavior.
[0185] The improvement of crystallization stability is due to the interaction between multiple liquid crystal dimer materials, and is not limited to the nematic liquid crystal monomer materials matched with them. Even if the nematic liquid crystal monomer material 5CB in material sample T-1 is replaced with other nematic liquid crystal monomer materials, this strong crystallization stability remains unchanged. The specific results are shown in Table 2 below:
[0186] Table 2
[0187]
[0188]
[0189] Example 3
[0190] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-7, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0191] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0192] The nematic liquid crystal monomer material is E7.
[0193] The chiral molecule is R811.
[0194] Example 4
[0195] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-8, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0196] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0197] The nematic liquid crystal monomer material is TEB300.
[0198] The chiral molecule is R811.
[0199] Example 5
[0200] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-9, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0201] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0202] The nematic liquid crystal monomer material is SLC1717.
[0203] The chiral molecule is R811.
[0204] Example 6
[0205] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-10, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0206] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0207] The nematic phase liquid crystal monomer material is HTD028200-200.
[0208] The chiral molecule is R811.
[0209] Example 7
[0210] A room temperature stable non-crystallized liquid crystal tilted helical material, named sample T-11, is made of the following components in percentage by weight: 45% liquid crystal dimer material, 52% nematic phase liquid crystal monomer material, and 3% chiral molecule;
[0211] The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
[0212] The nematic liquid crystal monomer material is SLC9023.
[0213] The chiral molecule is R811.
[0214] The room temperature stable non-crystallized liquid crystal tilted helical material of the present invention has long-term stability of physical parameters while maintaining ultra-high crystal stability. Sample T-1 prepared in Example 1 was filled into a commercial liquid crystal box (size: 15*18mm) containing an ITO electrode. 2 , thickness 12 μm), the dielectric constant (parallel dielectric ε ∥ , vertical dielectric ε ⊥ and relative dielectric constant Δε) and splay elastic parameter K 11 and bending elastic parameter K 33 . This method induces the liquid crystal to change from planar arrangement to vertical arrangement by applying an AC signal with a frequency of 1kHz. The capacitance of the sample is monitored as a function of the applied voltage. The external applied voltage varies from 0.1V to 8.5V, and the interval time of the voltage change is 30s. According to the theoretical fitting test capacitance and voltage dependence, the relative dielectric constant and elastic parameters can be extracted. The above tests on dielectric and elastic parameters are completed by a commercial liquid crystal comprehensive parameter tester (ALCT-IV1, INSTEC, USA). The results are as follows Figure 1 As shown, Figure 1 The figure is a schematic diagram of the dielectric constant and elastic parameter results of the room temperature stable non-crystallized liquid crystal tilted helical material of the present invention tested at different time stages during storage for 1 year. ∥ and ε ⊥They are approximately 14.6pN and 5.7pN respectively, and the relative dielectric constant Δε is approximately 8.9pN, which shows a positive liquid crystal. The molecules can be arranged along the electric field under the action of the electric field, satisfying one of the construction conditions of the tilted helix. Material system K 11 is about 11.0 pN. Most importantly, the material prepared by the present invention satisfies the ultra-low bending elastic constant, K 33 =0.3pN. This ultra-low bending elastic constant is a necessary condition for constructing the tilted helix, and plays a key role in the wide dynamic range modulation performance of the subsequent tilted helix structure reflective color. Moreover, even if the material is stored for a year, its measured physical parameters have almost no obvious changes, further confirming the ultra-high stability of the material system.
[0215] Furthermore, in order to verify the stability of the room temperature stable non-crystallized liquid crystal tilted helical material sample T-1 of the present invention, the electric field driven reflection band modulation performance of the tilted helical structure constructed by the invention was analyzed. The reflection spectrum of sample T-1 during a one-year storage period was tested along with the electric field driving. The results are as follows: Figure 2 shown. Figure 2 The figure is a schematic diagram of the reflection spectrum of the room temperature stable non-crystallized liquid crystal tilted helical material sample T-1 of the present invention during a storage period of one year as driven by an electric field. The tilted helical structure is constructed by applying an external electric field. As the external electric field strength increases from 0.52 to 1.33 V / μm, the pitch P and tilt angle θ of the tilted helical structure are compressed, accompanied by a sequential change of the reflected color to bright red, orange, green, cyan and dark blue, corresponding to the blue shift of its reflection spectrum. Its reflection spectrum can be reversibly and repeatedly operated within a wide spectral range of 450nm to 1050nm. Even after more than one year of storage and testing, the sample still has no crystallization. More encouragingly, the reflection spectrum corresponding to the corresponding electric field strength does not show obvious changes, confirming the strong stability of the tilted helical structure described in the present invention.
[0216] As a comparison, the electric field driven reflection band of the tilted helical material system constructed by the unstable material system (such as sample D-6 prepared in comparative example 9) was tested. The results are as follows: Figure 3 shown. Figure 3It is a schematic diagram of the electric field driven reflection band of the tilted spiral material system constructed by the room temperature stable non-crystallized liquid crystal tilted spiral material sample T-1 of the present invention and the sample D-6 prepared in comparative example 9. As can be seen from the figure, the room temperature stable non-crystallized liquid crystal tilted spiral material sample T-1 of the present invention has no crystallization even after being stored for 400 days, and no matter at any time point during the storage period, the reflection band modulation corresponding to the electric field is tested, whether it is the correspondence between the electric field and the reflection band position, or the overall modulatable spectral range, there is no obvious change. In contrast, the unstable sample sample D-6 prepared in comparative example 9 began to crystallize on the 20th day. Once crystallized, the modulation performance of the reflection band corresponding to the electric field rapidly degraded. It is manifested as the displacement of the electric field-reflection band position and the reduction of the overall reflection spectrum modulation range. This is caused by the gradual deterioration of the bending elasticity performance of the material system after the liquid crystal dimer material in the material system is crystallized and precipitated.
[0217] The room temperature stable non-crystallized liquid crystal tilted helical material of the present invention can form a liquid crystal tilted helical structure, which is a special helical structure formed under the drive of an electric field. Under the drive of an electric field, the reflection spectrum corresponding to the structure changes with the electric field intensity, and the reflection spectrum shows a wide dynamic range (450-1050nm) tunability. Figure 2 and Figure 3 The reflectance spectrum data in can confirm the existence of the liquid crystal tilted helical structure.
[0218] To further illustrate the above problem, the following polarizing microscope data is provided. Figure 4 As shown, Figure 4 This is a schematic diagram of the polarization microscope display results of the room temperature stable non-crystallized liquid crystal tilted helical material of the present invention. On the room temperature stable non-crystallized liquid crystal tilted helical material of the present invention, when no electric field is applied, the material system presents a planar helical structure of a traditional cholesteric phase liquid crystal, with almost no obvious specific reflection spectrum information; when an electric field is applied, the material is converted from a planar helical structure to a tilted helical structure, and for different electric field intensities, the pitch and inclination angle of the tilted helical structure corresponding to the structure change, thereby presenting a specific reflection color (red-green-blue) and a specific reflection spectrum position.
[0219] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A room temperature stable non-crystallized liquid crystal tilted helical material, characterized in that: It is made of the following components in percentage by weight: 45% of liquid crystal dimer material, 52% of nematic phase liquid crystal monomer material, and 3% of chiral molecules; The nematic liquid crystal monomer material is selected from 5CB, 8CB, 7OCB, E7, TEB300, SLC1717, SLC9023, HTD028200-200; The structure of 5CB is as follows: The structure of 8CB is as follows: The structure of 7OCB is as follows: The chiral molecule is selected from CB15, R811, S811, R2011, S2011, R1011, S1011, R5011, S5011; The structure of CB15 is as follows: The structure of R811 is as follows: The structure of S811 is as follows: The structure of R1011 is as follows: The structure of S1011 is as follows: The structure of R2011 is as follows: The structure of S2011 is as follows: The structure of R5011 is as follows: The structure of S5011 is as follows: The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 30% to 75%, CB9CB 15% to 45%, CB11CB 5% to 25%; The structure of CB7CB is as follows: The structure of CB9CB is as follows: The structure of CB11CB is as follows:
2. The room temperature stable non-crystallized liquid crystal tilted helical material according to claim 1, characterized in that: The liquid crystal dimer material is made of the following components in percentage by mass: CB7CB 40% to 60%, CB9CB 20% to 40%, and CB11CB 10% to 20%.
3. The room temperature stable non-crystallized liquid crystal tilted helical material according to claim 2, characterized in that: The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 20%, CB11CB 20%.
4. The room temperature stable non-crystallized liquid crystal tilted helical material according to claim 2, characterized in that: The liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 40%, CB11CB 20%.
5. The room temperature stable non-crystallized liquid crystal tilted helical material according to claim 2, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 50%, CB9CB 35%, CB11CB 15%.
6. The room temperature stable non-crystallized liquid crystal tilted helical material according to claim 2, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 55%, CB9CB 30%, CB11CB 15%.
7. Use of the room temperature stable non-crystallized liquid crystal tilted helical material according to any one of claims 1 to 6 in the preparation of display panels and display devices.
Citation Information
Patent Citations
Field induced and controlled heliconical structure of cholesteric liquid crystal
US20160252755A1